Fundamentals of rock mass classification systems used in engineering design - Rocca, Ricardo J. (2024)
Fil: Rocca, Ricardo J. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.